2017
DOI: 10.1016/j.bbrep.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic mitochondrial complex I exhibits aberrant hyperactivity in diabetes

Abstract: It is well established that NADH/NAD+ redox balance is heavily perturbed in diabetes, and the NADH/NAD+ redox imbalance is a major source of oxidative stress in diabetic tissues. In mitochondria, complex I is the only site for NADH oxidation and NAD+ regeneration and is also a major site for production of mitochondrial reactive oxygen species (ROS). Yet how complex I responds to the NADH/NAD+ redox imbalance and any potential consequences of such response in diabetic pancreas have not been investigated. We rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 102 publications
5
24
0
Order By: Relevance
“…Our data is contrasting with previous findings where the content of SIRT3 was heavily decreased in diabetic pancreas and lung [ 53 ], possibly the alterations in SIRT3 in diabetes are likely tissue dependent [ 54 ]. Moreover, when total mitochondrial protein acetylation profile was assessed by anti-acetylation western blot analysis, an increased acetylation on numerous proteins could be detected in diabetes [ 55 ], which corresponds with our results ( Figure 6 b).…”
Section: Resultssupporting
confidence: 89%
“…Our data is contrasting with previous findings where the content of SIRT3 was heavily decreased in diabetic pancreas and lung [ 53 ], possibly the alterations in SIRT3 in diabetes are likely tissue dependent [ 54 ]. Moreover, when total mitochondrial protein acetylation profile was assessed by anti-acetylation western blot analysis, an increased acetylation on numerous proteins could be detected in diabetes [ 55 ], which corresponds with our results ( Figure 6 b).…”
Section: Resultssupporting
confidence: 89%
“…As glucose flux through the polyol pathway consumes NADPH, it has been suggested that the level of NADPH could be significantly decreased . Indeed, we have found that this is the case in diabetic lung and pancreas, whereby NADPH content is lower than that in controls. It has been established that there is about a 15% decrease in NADPH in the diabetic lens .…”
Section: The Polyol Pathwaymentioning
confidence: 56%
“…So when NAD + levels decrease during diabetes, sirtuin activities will be decreased, and this can also be modulated by decreased expression of sirtuin proteins. Indeed, numerous studies including ours, have demonstrated attenuated expression of sirtuin proteins in diabetes . As a consequence, protein acetylation is increased (Figure A), leading to functional changes of numerous proteins .…”
Section: The Polyol Pathwaymentioning
confidence: 72%
“…In addition, it was found that defective complex I produces more ROS [ 96 ], suggesting that structural modifications of the enzyme may play a crucial role in ROS production process. Recently, it was reported that pancreatic mitochondrial complex I showed aberrant hyperactivity in type 1 and 2 STZ-diabetic mice and rat and in cultured β cells [ 97 ]. Further experiments focusing on STZ-induced diabetes in rats revealed that complex I′s hyperactivity could be attenuated by metformin.…”
Section: Resultsmentioning
confidence: 99%